Teaching Children to Let Nature to Just Be in Ecological Children's Picture Books by Kate Messner: An Ecocriticism Analysis - Ramadhina, Alisyah Putri; Tristanty, Anggie Ayu Isra; Hidayati, Nur; Saraswati , Rina (Universitas Airlangga, 2024)
Over and Under The Snow and Over and Under The Pond are children's picture books by Kate Messner that teach children life both and under certain terrains in this world that exist because of how nature works. This article aims to make readers understand the value of children's books and how they are an excellent way to teach about how nature works in this world. Ecocriticism is a theory that analyzes the works of authors, researchers, and poets in the context of environmental issues and wildlife. The Ecocriticism theory that is applied to this research is by Cheryll Glotfelty. This article uses a qualitative approach that describes the answers to the questions that have been collected. Over and Under The Snow and Over and Under The Pond are great books to teach children about how life is under The Snow and pond; these books help them to understand how to take care of the environment better since they would know we are not the only kinds to live in this world and how other non-human creatures struggle to survive the terrains nature have.